PENGARUH KUALITAS PELAYANAN DAN PROMOSI WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI AGEN SEMBAKO SAHABAT SETIA DI ERA PANDEMI COVID-19 - Agus Sri Iswiyanti; Dewi Puspita Sari; Hadi Mulyo Wibowo; Widya Nengsih (Sekolah Tinggi Manajemen IMMI Jakarta, 2023)
The cause of this observe changed into to decide whether or not provider excellent and phrase of mouth have an effect on shopping selections at Sahabat Setia grocery agents..The evaluation approach on this observe makes use of quantitative number one information, the check tiers achieved are Validity Test, Reliability Test, Normality Test, Multicollinearity Test, Heteroscedasticity Test, T Test, F Test, and Coefficient of Determination Test (R2). The information used on this observe is non possibility sampling with purposive sampling technique. The trying out device used is SPSS Version 25.The consequences of this observe suggest that the variables of Service Quality and phrase of mouth advertising have a big impact on Purchasing Decisions at unswerving pal grocery agents,